Crane accidents at construction site : causes and solution / Nurul Salwana Mohammad Sabri and Abdul Muhaimin Ab Wahid - Mohammad Sabri, Nurul Salwana; Ab Wahid, Abdul Muhaimin (2018)
Cranes, the lifting and handling equipment are vital in construction industry because without these machineries, construction cannot be done on time because some materials need to be use these machines to lift the materials. There are many accident failures in the construction area therefore the aim of this research is to find out the factors of crane fatalities at construction sites. The objectives of this research are to identify the causes of crane fatalities in the construction area, to determine the impacts of crane accidents towards workers and contractors and also to recommend the effective ways to prevent the accidents at construction area. To achieve these objectives, the data of this research has been collected through quantitative method by distributing questionnaires to the contractors and analyzed by SPSS version 23. The results found that the factors which causes the crane fatalities are the lack of maintenance of crane, and the security wire condition of the cranes The impacts of crane accidents contribution towards the highest risk of death and attitude of workers about ignorance of safety, it is compulsory for company to provide safety and health training are the effective ways to prevent the accidents.